A168 USE OF LEDIPASVIR/SOFOSBUVIR (LDV/SOF) WITH OR WITHOUT RIBAVIRIN (RBV) IN GENOTYPE 1 (GT 1) HCV-INFECTED PATIENTS POST LIVER TRANSPLANT (LT): EVALUATION OF SEVERAL REAL-WORLD DATASETS (RWD). (1st March 2018) - Bourliere, M; Charlton, M; Manns, M; Prieto, M; Fernandez, I; Londoño, M; Kwok, R; Smith, C; Ngo, H; Lee, S; Zhang, J; Arterburn, S; et al.
Abstract: Aims: Post LT patients infected with HCV are considered a hard-to-treat population. The FDA and Health Canada have recently approved treatment with LDV/SOF+RBV in GT1 LT recipients ± compensated liver disease based on SOLAR-1 & -2 data. Recent reports have shown that SVR rates achieved in HCV monoinfected patients in clinical trials are similar to that observed in real world cohorts, however this is yet to be demonstrated in post-LT patients. The goal of this analysis was to compare efficacy rates in real world cohorts to clinical trial data in this population. Methods: Integrated data on patients without cirrhosis or compensated cirrhosis who had undergone liver transplantation from 2 open-label phase-2 trials (SOLAR-1 and -2) was compared to 4 real-world datasets. Real-world cohorts included data from academic institutions, community medical centers and specialty pharmacies. Cohorts with less than 50 GT1 patients treated with LDV/SOF±RBV were excluded. Demographics, clinical characteristics, and SVR rates will be presented. Results: In SOLAR-1 & -2, patients were assigned to receive LDV/SOF+RBV for 12 or 24 weeks, with SVR 12 rates of 95% to 98%. There were no viral breakthroughs and 3 patients relapsed. Patients from 4 real-world cohorts received LDV/SOF±RBV for 8, 12 or 24 weeks. SVR 12 in the 4 real-world cohorts in patients treated with LDV/SOF±RBV for 8, 12 or 24 weeks ranged from 94–100%. RWD showed patients who received LDV/SOF without RBV had SVR rates of 94% - 96%, while those who received LDV/SOF with RBV had SVR12 rates of 96% - 100%. Viral relapse rates were low, ranging from 1–2% across all the RW cohorts. Conclusions: Evaluation of several heterogenous RWD shows comparable SVR12 rates to clinical trials. Patients with compensated liver disease post LT experience high cure rates of HCV with LDV/SOF±RBV. In addition, RWD showed GT1 patients who did not receive RBV had comparable SVR 12 rates to those did receive RBV with LDV/SOF. Funding Agencies: Gilead Sciences, Inc.